Turn Up the Heat—Food and Clinical Escherichia coli Isolates Feature Two Transferrable Loci of Heat Resistance - Boll, Erik J.; Marti, Roger; Hasman, Henrik; Overballe-Petersen, Søren; Stegger, Marc; Ng, Kim; Knøchel, Susanne; Krogfelt, Karen A.; Hummerjohann, Joerg; Struve, Carsten (Frontiers in Microbiology, 2017)
Heat treatment is a widely used process to reduce bacterial loads in the food industry or to decontaminate surfaces, e.g. in hospital settings. However, there are situations where lower temperatures must be employed, for instance in case of food production such as raw milk cheese or for decontamination of medical devices such as thermo-labile flexible endoscopes. A recently identified locus of heat resistance (LHR) has be shown to be present in and confer heat resistance to a variety of Enterobactericeae, including E. coli isolates from food production settings and clinical ESBL-producing E. coli isolates. Here, we describe the presence of two distinct LHR variants within a particularly heat resistant E. coli isolate raw milk cheese isolate. We demonstrate for the first time in this species the presence of one of these LHRs on a plasmid, designated pLHRFAM21805, also encoding type 3 fimbriae and three toxin/antitoxin systems. The plasmid was highly transferable to other E. coli strains, including Shiga-toxin-producing strains, and conferred LHR-dependent heat resistance as well as type 3 fimbriae-dependent biofilm formation capabilities. Selection for and acquisition of this “survival” plasmid by pathogenic organisms, e.g. in food production environments, may pose great concern and emphasizes the need to screen for the presence of LHR genes in isolates.